Mechanical and environmental performance comparisons of improved asphalt pavement wearing courses with high quality aggregates, steel slags, and polymeric compound. (13th June 2023) - Bosurgi, Gaetano; Celauro, Clara; Pellegrino, Orazio; Ruggeri, Alessia; Sollazzo, Giuseppe
Highlights: Steel slags was proven to be adequate for HMA surface courses, in high percentage. Steel slags can substitute efficiently basalt aggregates, typically used in the context. Steel slags use in HMA can increase sustainability and circularity of the industry. Mixtures with slags have advantages in technical, environmental and financial terms. Abstract: The use of waste materials in the construction of hot mix asphalt (HMA) pavements is an important opportunity for environmental sustainability. When properly designed, the alternative mixtures may also guarantee excellent mechanical performance. In this study, the results of an experimental analysis carried out on dense-graded HMAs are presented. In particular, the performance of a "traditional" surface mixture with limestone aggregate (designed with neat bitumen or a polymer-modified bitumen within the typical acceptance requirements for intended use in wearing courses) was compared with two alternative mixtures. The research investigated a surface mixture including coarse basaltic aggregates (a high-quality non-renewable resource) and one in which the coarse aggregate is substituted by a waste material, i.e. steel slags, in a high percentage. Both the improved mixtures included neat bitumen and a polymeric compound too, for advanced performance. Finally, for a more comprehensive comparison, a Life Cycle Assessment - LCA (cradle-to-gate approach) was carried out on the different mixtures, to compare the environmental impacts related to their production in asphalt plants, considering the features of the materials and fuels involved. The laboratory results showed comparable structural performance for the two mixtures with basalt aggregates and steel slag. In addition, other positive aspects concerned the higher crushing resistance of metal slag compared to basalt aggregates and the lower percentage of bitumen required by the proposed mixture with slags, with evident practical benefits. Furthermore, the LCA provided useful information about the environmental sustainability of the different mixtures, so that the feasibility of use of these recycled materials may be evaluated considering not only the technical and cost perspectives but the environmental ones too. The numerical results evidenced remarkable benefits for several impact categories for the mixtures with recovered waste materials, with promising advantages with their growing wide adoption.